Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Cheng, Lin (Zhejiang University Press, 2012)

(untitled)
Objective: High temperature adversely affects quality and yield of tomato fruit. Polyamine can alleviate heat injury in plants. This study is aimed to investigate the effects of polyamine and high temperature on transcriptional profiles in ripening tomato fruit. Methods: An Affymetrix tomato microarray was used to evaluate changes in gene expression in response to exogenous spermidine (Spd, 1 mmol/L) and high temperature (33/27 °C) treatments in tomato fruits at mature green stage. Results: Of the 10 101 tomato probe sets represented on the array, 127 loci were differentially expressed in high temperature-treated fruits, compared with those under normal conditions, functionally characterized by their involvement in signal transduction, defense responses, oxidation reduction, and hormone responses. However, only 34 genes were up-regulated in Spd-treated fruits as compared with non-treated fruits, which were involved in primary metabolism, signal transduction, hormone responses, transcription factors, and stress responses. Meanwhile, 55 genes involved in energy metabolism, cell wall metabolism, and photosynthesis were down-regulated in Spd-treated fruits. Conclusions: Our results demonstrated that Spd might play an important role in regulation of tomato fruit response to high temperature during ripening stage.